Ending the Stick and Embracing the Carrot: The Middle Way of Spin-Off Policy in Indonesian Islamic Banking - Sigit Pramono; Saiful Anwar; Adril Hakim; Aziz Budi Setiawan; Handi Risza; Gustofan Mahmud; Abdul Mujib Arijuddina (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2026)
The implementation of the P2SK Law has triggered debate over the mandatory spin-off of UUS from BUK into BUS. This study examines the arguments from both sides to identify potential areas of consensus. It finds that poor communication, particularly on the "purification" issue, has fueled disagreement. Consequently, stakeholders missed the chance to propose a voluntary spin-off mechanism to OJK. Such a proposal should be supported by affirmative government action to grow the Islamic banking sector. This study aims to critically integrate insights from literature and expert perspectives by examining competing arguments surrounding the spin-off policy to develop a robust and evidence-based direction for its optimal design and implementation. It employs a mixed methodology utilizing a structured literature review, in-depth interviews, and FGDs with key stakeholders selected through purposive sampling. The study also incorporates sentiment analysis and utilizes NVivo for thematic mapping and matrix coding. The findings reveal a high degree of discursive convergence between proponents and opponents, identifying the "Middle-Way Policy" as the primary area of consensus. The analysis shows that both groups align on the necessity of regulatory incentives ("carrots") and readiness-based criteria rather than forced compliance ("sticks") to ensure the sustainability and efficiency of the Islamic banking industry. This study recommends that the OJK needs to develop policies that reflect shared goals to expand the Indonesian Islamic banking market share. Importantly, it urges avoiding blanket mandatory spin-offs, as these may harm smaller UUS and unfairly burden regulators.